SEBUAH ANALISIS TEKNIK PENERJEMAHAN DALAM DIALOG DI FILM ENOLA HOLMES - Kurnia Aruning Nugrahani (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
At this time, there are still so many people in the world who cannot speak and understand the English language, especially Indonesian people. Because there are many differences in culture between English and Indonesia, and then factor that effect of translation. Furthermore, translation techniques also have an important to help people understand the meaning of the message from source language into target language contained in dialogues in the movie Enola Holmes. This study analyzing the translation techniques used in the dialogues in Movie “Enola Holmes” that was directed Harry Bradbeer. Based on the purpose this study is to identify types of the translation technique and to analysis translation technique are dominant to use by translator of translating from English to Indonesia in dialogues in the movie Enola Holmes. The theory utilized to analyzes the translation technique based on the theory Molina and Albir (2002). This study is qualitative descriptive. The findings of the study there are found fourteen translation techniques used by the translator, they are literal translation (38.7%), linguistic amplification (19.3%), established equivalent (9.7%), modulation (5.4%), generalization (4.7%), compensation (4.4%), linguistic compression (3.8%), adaptation (3.2%), transposition (3.0%), amplification (2.8%), borrowing (2.6%), particularization (1.1%), reduction (0.8%), calque (0.5%). From the result, the writer can conclude that translation techniques are dominant used by translator of this study is literal translation.